Physical Characteristics of Active Packaging Based on Methyl Cellulose with The Addition of Glutaraldehyde and Klutuk Banana (Musa balbisiana Colla) leaf extract - Rahmadhia, Safinta Nurindra; Santoso, Umar; Supriyadi, Supriyadi (Universitas Muhammadiyah Yogyakarta, 2019)
Klutuk banana leaf is widely used as food packaging material since it has large size and not easily torn. Many traditional packaging materials are recently abandoned, thus it is necessary to develop an active packaging having an advantage of synthetic packaging. This study aimed to create active packaging from methylcellulose (MC) added with glutaraldehyde (GA) and Klutuk banana leaf extract (EDPK), as well as to determine its properties and antioxidants. The casting method with GA as a crosslinker and EDPK as an antioxidant agent was used to make film/active packaging. Banana Klutuk leaves were dried using cabinet dryer for 24 hours and the leaf powder was extracted using maceration method with methanol 80%. The extract was concentrated with a rotary evaporator to be tested for its antioxidant capacity. The results showed that the film with EDPK addition exhibited dark green color. Tensile strength values increased when EDPK and GA were added at concentrations of 30 and 45%. However, EDPK film elongation was not affected by GA addition. Addition of EDPK decreased thermal stability by 25-45 oC, whereas the addition of GA improved thermal stability by 5-25 oC. Antioxidants in banana leaf extract can migrate to 10 and 50% simulant ethanol.Â